Peran Masyarakat dalam Pencegahan Peredaran Narkotika - Maretha Lintang Putri Praptisi (Pusat Riset dan Inovasi Nasional, 2025)
Optimal legal protection for an informed society must be equated with the role of society in supporting law enforcement to prevent and eradicate the protection of illicit drug trafficking and drug precursors. Law enforcement that has the ability to act and inform the authorities of everything that happens in society and optimize the critical community functions needed. The researcher's goal is to find out how society contributes to the prevention and protection of narcotics. The researcher uses library research, or normative legal research, in this study. Data are collected through analysis, observation, and investigation of documents. This produces various figurative (secondary) data, such as decisions, legal concepts, regulations, and opinions from experts and scientists.